Identification of Shale Layer in Offshore Field of North East Java Basin for Non-Conventional Oil and Gas Exploration - Ordas Dewanto; Nanda Paquita Syaharani; Darsono Darsono; Andy Setyo Wibowo (Department of Physics, Sebelas Maret University, 2024)
Non-conventional hydrocarbon exploration is one way to develop shale potential to increase oil and gas reserves in Indonesia. Shale is a rock that is rich in organic material and is a target for non-conventional exploration, because it functions as a source and reservoir rock with a large shale volume and low permeability. Isopach maps can represent the thickness of shale layers and have the potential to become non-conventional exploration targets located in thick shale layers. Based on this background, this research will identify shale layers in the offshore fields of the North East Java Basin for non-conventional oil and gas exploration. The methods used are well logging and seismic methods. This research focuses on determining the location of shale layer depocenters based on isopach maps as a first step in localizing areas that will be targeted for the development of non-conventional hydrocarbon exploration. This research uses 29 2D seismic lines and 2 well data, namely NP-1 and NP-2 wells and the research target is the Kujung Formation and Ngimbang Formation in the offshore area of the North East Java Basin. The results obtained from the isopach map show that the depocenter location of the Kujung Formation is in the northwest direction with a shale thickness of 600-800 meters, while the Ngimbang Formation is in the east direction with a shale thickness of 1000-1300 meters. From the depocenter location, it can be seen that this location has a wealth of organic material so it has the potential to become a source rock and reservoir.